The effectiveness of a self-regulation program in improving the quality of university life among female students with physical disabilities - Mohamed Mosaad A. Metawee; Zienab M. Shokier (International Journal of Advanced Humanities Research)
This study aimed to improve self-regulation (SR) among Female students with Physical disabilities and identify the effects of self-regulation on the Quality of University Life (QUL). A full sample of Study included 157-Female students with physical impairments (Mage=19.50; SD=1.46). The participants completed measures for self-regulation and quality of university life by self-regulation scale (SRS) and quality of university life scale (QULS), in 2022 in Saudi Arabia. We randomly selected 54 Female students with disabilities (Mage= 19.76; SD= 1.33): the intervention group (N= 27), and wait-list group (N= 27). The intervention contains 18-sessions, 3-times a week for 6-weeks. The results of the survey study showed a strong lack for self-regulation and quality of life among female students with disabilities. The results showed that the Female students with physical disabilities in the intervention group (self-regulation training group) showed greater improvement for self-regulation and quality of university life (subscales) in the post-test compared to the pre-test, and compared to the wait-list group. The present Findings provided important evidence for the effectiveness of self-regulation training for improvement of Quality of university Life among Female students with physical disabilities